Method of gas detection applied to infrared hyperspectral sensor - Kastek, Mariusz; Piątkowski, Tadeusz; Dulski, Rafał; Chamberland, Martin; Lagueux, Philippe; Farley, Vicent (Photonics Letters of Poland, 2012)
This paper presents detection and identification of gases using an infrared imaging Fourier-transform spectrometer. The principle of operation of the spectrometer and the method for gases detection and identification has been shown in the paper. The variation of a signal reaching the IFTS caused by the presence of a gas has been calculated and compared with the reference signal obtained without the presence of a gas in IFTS’s field of view. Some result of the detection of various types of gases has been presented too. Full Text: PDF References V. Farley, M. Chamberland et al., "Chemical agent detection and identification with a hyperspectral imaging infrared sensor", Proc. SPIE 6661, 66610L (2007). CrossRef A. Vallières, A. Villemaire et al., "Algorithms for chemical detection, identification and quantification for thermal hyperspectral imagers", Proc. SPIE 5995, 59950G (2005). CrossRef M. Chamberland, C. Belzile et al., "Advancements in field-portable imaging radiometric spectrometer technology for chemical detection", Proc. SPIE 5416, 63 (2005). CrossRef V. Farley, C. Belzile et al., "Development and testing of a hyperspectral imaging instrument for field spectroscopy", Proc. SPIE 5546, 29 (2005). CrossRef P. Tremblay, S. Savary et al., "Standoff gas identification and quantification from turbulent stack plumes with an imaging Fourier-transform spectrometer", Proc. SPIE 7673, 76730H (2010). CrossRef M. Kastek, T. Sosnowski et al., "Multispectral gas detection method", WIT Transactions on Ecology and the Environment 123, 227 (2009). CrossRef M. Kastek, T. Piątkowski, P. Trzaskawka et al., "Infrared imaging fourier transform spectrometer as the stand-off gas detection system", Metrol. Meas. Syst. XVIII, 4 (2011). DirectLink